2019
DOI: 10.21608/bvmj.2019.111628
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and hepatoprotective effects of chitosan nanoparticles against hepatotoxicity induced in rats

Abstract: This study was conducted to investigate the preventive effects of Chitosan-nanoparticles on diethylnitrosamine (DEN) induced hepatotoxicity in albino rats. Forty male albino rats were divided into four groups: group (1): normal control, group (2): group (2): hepatotoxic rats administrated DEN orally (20 mg/kg b.wt/ day), group (3): rats receive chitosan-nanoparticles orally and group (4): Hepatotoxic rats were treated with chitosan-nanoparticles orally at a dose of (200 mg / kg bw/day). All animals were sacrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Regardless, a dose-dependent amelioration was observed in the hepatic ALP activity, while the AST and ALT activities were equally improved in the groups supplemented with chitosan. This observation is consistent with other studies which suggested the hepato-protective role of chitosan [37,38]. Intriguingly, as observed in this study, hepatic ALT reduced significantly in the normal + 5% chitosan group compared to the normal diet group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regardless, a dose-dependent amelioration was observed in the hepatic ALP activity, while the AST and ALT activities were equally improved in the groups supplemented with chitosan. This observation is consistent with other studies which suggested the hepato-protective role of chitosan [37,38]. Intriguingly, as observed in this study, hepatic ALT reduced significantly in the normal + 5% chitosan group compared to the normal diet group.…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, we are the first to report the ameliorative effects of chitosan on hyperlipidemia-invoked kidney injury. Akin to AST and ALT, ALP is a marker enzyme for hepatobiliary damage and hepato-necrotic injury which might leak out from the damaged hepatic cells [37]. Accordingly, hepatic AST, ALT, and ALP (Figure 2) decreased in the HFD-untreated group in this study.…”
Section: Discussionmentioning
confidence: 51%
“…The hepatoprotective effects of chitosan and chitosan nanoparticles were also noted in liver injuries induced by various hepatotoxic substances, such as diethylnitrosamine in rats [70] and emamectin benzoate in mice [71]. The rats treated with chitosan had reduced levels of serum liver marker enzymes and increased activity of antioxidant parameters and of serum albumin in animals with diethylnitrosamine-induced liver toxicity [70]. The use of chitosan and chitosan nanoparticles amended the blood biochemical modifications, reduced the oxidative stress, decreased the expression of some specific genes in liver with a decreasein elevated DNA damage and improved the structural hepatic alterations [71].…”
Section: Discussionmentioning
confidence: 97%
“…The hepatoprotective effects of chitosan and chitosan nanoparticles were also noted in liver injuries induced by various hepatotoxic substances, such as diethylnitrosamine in rats [70] and emamectin benzoate in mice [71]. The rats treated with chitosan had reduced levels of serum liver marker enzymes and increased activity of antioxidant parameters and of serum albumin in animals with diethylnitrosamine-induced liver toxicity [70].…”
Section: Discussionmentioning
confidence: 99%
“…Also, The result agreed with what he indicated [21], who found great increase in The value of hepatic enzymes (ALT, ALP , ALP), which are sensitive indicators for many diseases, including heart disease and hepatomegaly. AST zim is (45.5-80.5) IU/L [21] He also indicated [22] that the group of animals fed on soft cheese had a low concentration of enzymes (ALP, AST, and ALT) well due to the low role of fatty acids present in cheese Increase the efficiency of the work of the liver The results converged was found by [23], When they said that the level of liver enzymes is dropping dramatically AST ALP ALT at experimental animals nanoparticles of selenium for a period of twenty-eight days And this is the result for this to the ability of selenium nanobodies to enhance the self-against oxidative processes. About an increase in the values of liver enzymes as a result of a defect in the liver tissue as a result of taking medications selenium nanoparticles.…”
Section: The Effect Of Different Treatments On Liver Enzymes Of Exper...mentioning
confidence: 99%